Disputes around the concept of postmemory in criticism of the narrative of children of militants of the 70s (El Taco en la Brea, 2025)
This article aims to investigate the main lines deployed by critics to read the narrative of daughters and sons of Argentine militants of the 70s with the objective of identifying the hegemonic areas of dispute and consensus around, mainly, the concept of postmemory. The tensions between memory and postmemory; the interest in those texts that fictionalize the experience of loss more than in those that are inscribed in the testimonial; the focus on childhood and its circumstances as axes of analysis are some of the issues that persistently appear in criticism, thus consolidating a corpus in which certain genres, topics and modalities of intervention on the recent past are privileged.
Keywords: argentine literature; second generation; postmemory; autofiction; controversies